THE EFFECT OF ASSET STRUCTURE, SALES GROWTH AND NET PROFIT MARGIN ON THE CAPITAL STRUCTURE OF INFRASTRUCTURE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2019–2023 - Ayu Namira Sasti; Wardhiah; Darmawati Muchtar; Zulfan (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
The purpose of this study is to determine the effect of asset structure, sales growth, and net profit margin on the capital structure of infrastructure companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The data used in this study are secondary data. The population in this study was 58 companies and the sample used was 26 companies selected using purposive sampling technique, resulting in a total of 150 observations. The data analysis method used was panel data regression. The results of the study indicate that partially the asset structure has a negative and insignificant effect on the capital structure of infrastructure companies for the 2019-2023 period. Meanwhile, sales growth has a negative and significant effect on the capital structure of infrastructure companies for the 2019-2023 period and net profit margin has a negative and significant effect on the capital structure of infrastructure companies for the 2019-2023 period.